Rapid flipping between electrolyte and metallic states in ammonia solutions of alkali metals - Vitek, Marco; Rončević, Igor; Marsalek, Ondrej; Schewe, H Christian; Jungwirth, Pavel (Nature communications, 2025)
Nonmetal-to-metal transitions are among the most fascinating phenomena in material science, associated with strong correlations, large fluctuations, and related features relevant to applications in electronics, spintronics, and optics. Dissolving alkali metals in liquid ammonia results in the formation of solvated electrons, which are localised in dilute solutions but exhibit metallic behaviour at higher concentrations, forming a disordered liquid metal. The electrolyte-to-metal transition in these systems appears to be gradual, but its microscopic origins remain poorly understood. Here, we provide a detailed time-resolved picture of the electrolyte-to-metal transition in solutions of lithium in liquid ammonia, employing ab initio molecular dynamics and many-body perturbation theory, which are validated against photoelectron spectroscopy experiments. We find a rapid flipping between metallic and electrolyte states that persist only on a sub-picosecond timescale within a broad range of concentrations. These flips, occurring within femtoseconds, are characterised by abrupt opening and closing of the band gap, which is connected with only minute changes in the solution structure and the associated electron density.